2022
DOI: 10.33687/jpe.3995
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Screening of Hybrids and Synthetic Maize (Zea mays L.) Cultivars for Drought-Sensitive and Drought-Tolerant Under Different Irrigation Regimes

Abstract: Water scarcity is the most serious issue in crop production around the globe. Because of less water availability, various breeding and agronomic management techniques are being used to cope with this issue. For this purpose, a pot experiment was performed to screen hybrids and synthetic maize cultivars for drought-tolerance under various irrigation regimes at green-house of Agronomic Research Farm, Bahauddin Zakariya University, Multan, Pakistan during 2017. Experimental treatments comprise five maize hybrids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Similar results were reported by Iqbal et al (2010). Shah et al (2022) reported similar results regarding spike length. Mirbahar et al (2009) reported that skipping irrigation at different crop growth stages significantly affects spike length and spike weight of wheat cultivars.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were reported by Iqbal et al (2010). Shah et al (2022) reported similar results regarding spike length. Mirbahar et al (2009) reported that skipping irrigation at different crop growth stages significantly affects spike length and spike weight of wheat cultivars.…”
Section: Discussionsupporting
confidence: 90%